Prospects for the clinical application of exosomal circular RNA in squamous cell carcinoma - Wang, Rongzhong; Wang, Shiyan; Jiang, Hua; Lan, Yingmei; Yu, Shaobin (Frontiers in Oncology, 2024)
Squamous cell carcinoma (SCC) is a prevalent malignancy affecting multiple organs in the human body, including the oral cavity, esophagus, cervix, and skin. Given its significant incidence and mortality rates, researchers are actively seeking effective diagnostic and therapeutic strategies. In recent years, exosomes and their molecular cargo, particularly circular RNA (circRNA), have emerged as promising areas of investigation in SCC research. Exosomes are small vesicles released into the extracellular environment by cells that contain biomolecules that reflect the physiological state of the cell of origin. CircRNAs, known for their unique covalently closed loop structure and stability, have garnered special attention in oncology and are closely associated with tumorigenesis, progression, metastasis, and drug resistance. Interestingly, exosomal circRNAs have been identified as ideal biomarkers for noninvasive cancer diagnosis and prognosis assessment. This article reviews the progress in research on exosomal circRNAs, focusing on their expression patterns, functions, and potential applications as biomarkers in SCC, aiming to provide new insights and strategies for the diagnosis and treatment of SCC.